Cell biology of diabetic nephropathy: Roles of endothelial cells, tubulointerstitial cells and podocytes. Issue 1 (11th July 2014) - Maezawa, Yoshiro; Takemoto, Minoru; Yokote, Koutaro
Abstract Diabetic nephropathy is the major cause of end‐stage renal failure throughout the world in both developed and developing countries. Diabetes affects all cell types of the kidney, including endothelial cells, tubulointerstitial cells, podocytes and mesangial cells. During the past decade, the importance of podocyte injury in the formation and progression of diabetic nephropathy has been established and emphasized. However, recent findings provide additional perspectives on pathogenesis of diabetic nephropathy. Glomerular endothelial damage is already present in the normoalbuminuric stage of the disease when podocyte injury starts. Genetic targeting of mice that cause endothelial injury leads to accelerated diabetic nephropathy. Tubulointerstitial damage, previously considered to be a secondary effect of glomerular protein leakage, was shown to have a primary significance in the progression of diabetic nephropathy. Emerging evidence suggests that the glomerular filtration barrier and tubulointerstitial compartment is a composite, dynamic entity where any injury of one cell type spreads to other cell types, and leads to the dysfunction of the whole apparatus. Accumulation of novel knowledge would provide a better understanding of the pathogenesis of diabetic nephropathy, and might lead to a development of a new therapeutic strategy for the disease.